2021
DOI: 10.3389/fphys.2021.725716
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Broadband Forcecardiography Sensor for Simultaneous Monitoring of Respiration, Infrasonic Cardiac Vibrations and Heart Sounds

Abstract: The precordial mechanical vibrations generated by cardiac contractions have a rich frequency spectrum. While the lowest frequencies can be palpated, the higher infrasonic frequencies are usually captured by the seismocardiogram (SCG) signal and the audible ones correspond to heart sounds. Forcecardiography (FCG) is a non-invasive technique that measures these vibrations via force sensing resistors (FSR). This study presents a new piezoelectric sensor able to record all heart vibrations simultaneously, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 73 publications
(105 reference statements)
0
61
0
Order By: Relevance
“…Several sensor references were analyzed such as the Tekscan A-201, the Ohmite FSR03CE and the Interlink FSR400. These sensors were selected based on our own experience and after having made a small state of the art of the existing sensors [ 29 , 30 ]. Important criteria were reliability through hysteresis (change in behavior during use), sensitivity (minimum force required to read data), force sensitive area and stability (defined here as “at rest” resistance).…”
Section: Discussionmentioning
confidence: 99%
“…Several sensor references were analyzed such as the Tekscan A-201, the Ohmite FSR03CE and the Interlink FSR400. These sensors were selected based on our own experience and after having made a small state of the art of the existing sensors [ 29 , 30 ]. Important criteria were reliability through hysteresis (change in behavior during use), sensitivity (minimum force required to read data), force sensitive area and stability (defined here as “at rest” resistance).…”
Section: Discussionmentioning
confidence: 99%
“…The chest wall vibrations caused by the mechanical activity of the beating heart are measured using the novel forcecardiography (FCG) method [ 10 , 11 ]. This method can acquire a low-frequency signal component that conveys essential information about the heart’s empty dynamics and ventricular filling.…”
Section: Cardio-mechanical Signalsmentioning
confidence: 99%
“…This method can acquire a low-frequency signal component that conveys essential information about the heart’s empty dynamics and ventricular filling. FCG is obtained by attaching force sensors to a patient’s chest wall [ 10 , 11 ]. The force-sensitive resistors are used in FCG sensors, which have previously been used to monitor muscle contractions and recognize various hand motions.…”
Section: Cardio-mechanical Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed the high similarity between the EMG-LE and the signal obtainable from a custom force sensor capable of detecting the mechanical activity of muscles (referred to as force-myography (FMG)) [24]. The advantages deriving from the use of FMG instead of EMG are various [25]: the problems related to EMG recording and its processing are avoided; the force sensor output can be used as is (no processing is required) and has already been successfully demonstrated for various applications (hand prosthesis control [26][27][28][29]; hand gesture recognition [30,31]; physiological parameters monitoring [32][33][34]); moreover, a very recent study suggests that force sensors seem to perform better than EMG in daily activities for exoskeleton controls [35].…”
Section: Introductionmentioning
confidence: 99%